Inhibition of Internal Attention to Positive and Negative Representations in Dysphoria1. (14th April 2018) - Isato, Ayako; Nishimura, Haruki; Yamada, Makiko; Mochizuki, Satoshi
Abstract: We developed the Internal–External Attention‐Switching Task, which measures the ability to inhibit internal attention and the ability to remove inhibition of internal attention. The Internal–External Attention‐Switching Task was administered to a sample of dysphoric and non‐dysphoric undergraduate or graduate students ( N = 44). Difficulty in both inhibition of internal attention to negative representation and removal of this inhibition were shown to be general. Importantly, however, dysphoric individuals could not maintain internal attention or remove inhibition of internal attention to positive representations as easily as non‐dysphoric individuals could. Therefore, reduced attention to positive representations in dysphoric individuals may enable maintenance of their depressive mood.